Analisis Perbandingan Biaya Alat Gali Muat Excavator Komatsu PC 1250 dengan Excavator Hitachi ZX 1200 Pada Pengupasan Overbarden Di PT. Artamulia Tatapratama - Ichsan Achmad Setiawan; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. PT. Artamulia Tatapratama utilizes Komatsu PC 1250 and Hitachi ZX 1200 excavators for the process of stripping and transporting overburden which has a working combination where each excavator serves six units of Komatsu HD 465 dump trucks. This research aimed at: 1) obtaining the productivity value of the excavator and dump truck, 2) obtaining owning and operational costs of Komatsu PC 1250 and Hitachi ZX 1200 excavators, and 3) determining more economical excavators. The process of data analysis and processing in this study included: 1) calculation of ownership and operational costs, 2) calculation of productivity of the dump trucks, 3) calculation of production costs, and 4) comparative analysis of production costs. Based on the results obtained, the cost of overburden stripping using Hitachi ZX 1200 excavator was more economical than Komatsu PC 1250 excavator. It is recommended to PT. Artamulia Tatapratama to use the Hitachi ZX 1200 excavator in the overburden stripping process. In addition, in terms of the procurement of further equipment, the company is advised to choose the Hitachi ZX 1200 excavator since it is more economical.Keywords: Owning Cost, Operation Cost, Productivity, Production Costs,Excavator